Potato (Solanum tuberosum L.) can be grown safety on human consumption in slight Hg-contaminated soils across China mainland - Bo Yang (Nature Portfolio, 2020)
Abstract Mercury (Hg) exposure poses serious health risks to humans, resulting in extensive investigations examining Hg accumulation, biotransformation and uptake in crops. In this investigation, Hg accumulation in potato tubers due to bioaccumulation processes was determined and bioconcentration factors affecting bioaccumulation were identified using a greenhouse experiment. Our results showed that the percentage of available Hg concentrations from total Hg in soil samples were less than 1.2%, indicating that soils used in our experiment exhibited a high binding strength for Hg, with alkaline soil recording the lowest available Hg/total Hg ratio. Results indicated that soil type and Hg treatment, as well as their interactions, significantly affected Hg accumulation in potato tubers (P < 0.01). Importantly, our results also indicated that potatoes grown in soil with a Hg concentration two times higher than the Chinese Environmental Quality Standard exhibited no obvious toxic effects on humans; Bioconcentration factors (BCF) values (<0.04) suggested that potatoes can be considered as a low Hg accumulating species and suitable for human consumption. Potato yields in acidic soil were lower than those in neutral or alkaline soils, making this medium unsuitable for growth.